Case Report of a New Headache Developed by a Combat Soldier after an Episode of Exertional Heat Illness - Schermann, Haggai; Sherman, Mikhail; Rutenberg, Ran (Frontiers in Neurology, 2017)
Only a few authors have reported about a new-onset headache among patients who sustained an episode of an Exertional Heat Illness (EHI). This report presents a healthy and physically fit 20-year-old male who developed a completely new headache after an EHI event. The new headache could be aggravated or called by exertion or exposure to sun and environmental heat. It was severe enough to interfere with even moderate physical activity, but reacted well to a few hours’ rest and OTC pain medications. An extensive work-up including laboratory blood tests, lumbar puncture, head CT and CT angiogram was negative. The patient remained symptomatic on the 6-month follow-up. Continued abstinence from physical activity and waiting for spontaneous resolution were recommended. We suggest that the headache may be secondary to the hyperthermia brain damage during the EHI event, and differs from exertional headache by its association with exposure to sun and environmental heat.